Class Action as a Strategy for Saving Waqf Land Assets in Indonesia - Rimanto, Rimanto; Hidayatullah, Kholid (Universitas Islam Sultan Agung, 2022)
The legal events of waqf that take place are often not accompanied by awareness of an accountable administration, thus triggering the heirs to take back the waqf assets on the grounds that the assets are the personal assets of their parents. From this case, it is necessary to have a legal breakthrough, so that the waqf assets remain public assets, so that the eternal value of the waqf will continue to be maintained. This research is focused on finding the construction of salvage waqf assets that do not have adequate legality from reclaiming efforts by wakif heirs. The purpose of this study is to find out what regulations regulate waqf land objects for which there is no formal legality and to find legal procedures that can be used to maintain waqf land for which there is no formal legality in order to maintain its immortality aspect. The method used is qualitative analysis and the results are presented descriptively. The constructive pattern of saving waqf assets is by looking for legal opportunities or ways that can be taken by the community or community groups, by examining several Supreme Court regulations, the Law of Religious Courts Procedure, and Law Number 41 of 2004 concerning Waqf, as the primary data source. Based on PERMA No. 1 of 2002, PERMA regulates the mechanism for class action with civil proceedings that have the right to provide procedural rights for a person or group to become a plaintiff in order to fight for disputes that cause harm and suffering to many people. The results of the study concluded that class action is an alternative procedure that can be used as a solution in saving waqf assets acquired by wakif heirs, due to the absence of adequate waqf evidence